ORGANIZATIONAL COMMITMENT: LOYALTY AND NEGLECT MODEL OF EMPLOYEES RESPONSE TO ORGANIZATIONAL CULTURES - Rajiani, Ismi; Abdul Aziz, Azah (2012)
This paper proposes the model of Exit, Voice, Loyalty, and Neglect (EVLN) as manifestation of employees’ organizational commitment (EOC) in responding to organizational cultures within Malaysian setting. Structural equation modelling is used to fit the data provided by 150 offices employees of manufacturing companies. The best predictions are proposed for loyalty and neglect. Loyalty is expected to be found in organizations that value the organizational culture dimensions of team work, respect for people, stability, attention to details and outcome orientation. The findings have important implications for practitioners attempting to improve the level of EOC of their employees which in turns to enhance the level of loyalty contributing to improvements in productivity and growth in the Malaysian manufacturing industry.